An Economic Model of Sustainable Development in the Russian Arctic: The Idea of Building Vertical Farms - Nikolay Didenko; Djamilia Skripnuk; Igor Ilin; Vitally Cherenkov; Alexander Tanichev; Sergei V. Kulik (Agronomy, 2021)
The main aim of the article is to find out the key factors of sustainable development of the Russian Arctic, which is strategically significant for Russia. The academic literature was reviewed to find out the time dynamics of the references to the economic models suitable for achieving the goals of sustainable development, and there has been hyperbolic growth in the attention paid to similar problems all around the world. The article compares three relatively new economic models in order to understand which of them is the most applicable to the promotion of sustainable development in the Russian Arctic: (a) bioeconomy, (b) green economy and (c) circular economy. The analysis of the relevant sources shows that the model of the circular economy is preferable for the Russian Arctic. Most of the article is dedicated to understanding the sources and mechanisms of the circular economy. The schematic description of vertical greenhouses and possibility of using vertical farms are presented in the paper as an example of organization of local food production according to the principles of the circular economy. The article considers a modeled project of creating a vertical farm in the Russian Arctic and a simulated indicator—profit of the vertical farm.